Gong Luwang of the Village of Kesiut Tabanan, in a Historical Perspective and Wayang Lemah in the Temple Festival of the Pura Dasar Bhuwana Gelgel - PARTO, Fx. Suhardja (FSP ISI Yogyakarta, 1985)
R. Skripsi